2015
DOI: 10.1039/c4gc02246g
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic recovery of elements from complex mixtures using deep eutectic solvents

Abstract: The dissolution and subsequent selective recovery of elements from complex mixtures naturally necessitates redox chemistry. The majority of processes involve hydrometallurgical dissolution followed by selective chemical precipitation or electrochemical winning. The atom and energy efficiencies of these processes are poor, leading to a large volume of aqueous waste which needs to be treated before disposal. In this study it is demonstrated that electrocatalysis is an atom effective method of carrying out digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 40 publications
0
85
0
2
Order By: Relevance
“…The I 2 /I -redox couple is a strong oxidizing agent in the DES choline chloride: ethylene glycol (1:2 molar ratio) [24]. A process has been developed to dissolve polymetallic waste using an electrocatalytic oxidation by iodine [128]. After the oxidation, the iodide is reoxidized to iodine at the anode.…”
Section: Ionometallurgical Processesmentioning
confidence: 99%
“…The I 2 /I -redox couple is a strong oxidizing agent in the DES choline chloride: ethylene glycol (1:2 molar ratio) [24]. A process has been developed to dissolve polymetallic waste using an electrocatalytic oxidation by iodine [128]. After the oxidation, the iodide is reoxidized to iodine at the anode.…”
Section: Ionometallurgical Processesmentioning
confidence: 99%
“…14,28,29 Pyrite oxidation consists of three steps: a cathodic reaction, an electron transfer and an anodic reaction. If oxygen is the oxidant then the cathodic reaction is the reduction of oxygen, which is followed by electron transfer to the iron centre followed by a reaction of the sulfur with water and oxygen to make the sulfate anion, the overall reaction being:…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…11,12 It has also been shown that they can be used for direct electroreduction of copper oxide to copper 13 and for the electrocatalytic dissolution and recovery of metals from alloys. 14 Recently we have shown that iodine in DESs can be used to selectively solubilise minerals from ore samples. 15 It has been shown that DESs can be used on a large scale to recover Zn and Pb from arc furnace dust waste.…”
Section: Introductionmentioning
confidence: 99%
“…[184,185] Forexample,the use of Lewatite S100 as an ion-exchange resin easily removes > 96 %o ft he Fe and Ni. [192,193] Ionic liquids allow only one or at most afew elements to be separated selectively.F or example, 1-butyl-3-methylimidazole hexafluorophosphate (([Bmim]-[PF 6 ]) proved suitable for extracting Pt IV and Pd II from asolution of Au III .Extraction rates for platinum are reported to reach 80 %. Solvent extraction processes employ conventional compounds,such as triisobutylphosphine sulfide (TIBPS) and di-(2-ethylhexyl)phosphorica cid (DEHPA), which reliably transfer > 99 %ofthe Pd into the organic phase.Inprinciple, the same applies to Pt, when thiosulfate is added for reextraction.…”
Section: Extraction Technologiesmentioning
confidence: 99%